The green innovation and ESG performance: evidence from the new generation of information technology in China - Wang, Shenglian; Zhang, Xiaoyuan; Raja Ahmad, Raja Adzrin; Azmi, Nurul Azlin (UiTM Cawangan Johor, 2024)
In light of growing environmental and social concerns worldwide, environmental, social, and governance (ESG) disclosure is an issue of transparency and shows a firm's commitment to sustainable development. This study examines the relationship between green innovation, sustainability strategy, and ESG performance, focusing on the moderating role of sustainability strategies. Using a sample of 381 new-generation information technology firms in China from 2018 to 2023, our results suggest the following: (1) Strong evidence of a positive relationship between green innovation and ESG performance. (2) The sustainability strategies significantly improve the performance of ESG. 3) The sustainability strategies positively strengthen the correlation between green innovation and ESG performance. This research also contributes to stakeholders' consideration of investing in green innovation and setting up long-term sustainability strategies in their firms to improve ESG performance.